Infrared, Millimeter-Wave, and Terahertz Technologies V 2018
DOI: 10.1117/12.2501217
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dependence of terahertz generation in jets of water and ethanol mixtures

Abstract: In this work, we considered mixtures of ethanol and water in the form of jets as samples for THz generation based on laser-induced filamentation. The dependence of the output energy of terahertz radiation on the concentration of ethanol in water was experimentally studied. It is shown that the energy grows linearly, which can be explained by an increase in the ionization energy due to the linear replacement of low-efficient charge carriers (water) with highlyefficient (ethanol). The dependence of the THz gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In addition, it has been shown that the exposure of water or aqueous-alcoholic solutions of various concentrations to a laser leads to emission in the THz region [8,71], that is, a physical effect on a liquid leads to specific radiation of the liquid. When extremely diluted solutions are obtained, a certain physical effect (vibrational action in the presence of the initial substance) is also exerted on the initial and subsequent solutions, which leads to a change in their physical-chemical properties [2,[72][73][74][75], and, consequently, the solutions in general.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that the exposure of water or aqueous-alcoholic solutions of various concentrations to a laser leads to emission in the THz region [8,71], that is, a physical effect on a liquid leads to specific radiation of the liquid. When extremely diluted solutions are obtained, a certain physical effect (vibrational action in the presence of the initial substance) is also exerted on the initial and subsequent solutions, which leads to a change in their physical-chemical properties [2,[72][73][74][75], and, consequently, the solutions in general.…”
Section: Discussionmentioning
confidence: 99%